PERAN LITERASI KEUANGAN SYARIAH DAN FINANCIAL SELF-EFFICACY DALAM MEMBENTUK PERILAKU KEUANGAN MAHASISWA - Dian Sahpitri; Budi gautama Siregar; Azwar Hamid; Aswadi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2026)
This study aims to analyze the effects of Islamic financial literacy and financial self-efficacy on the financial behavior of students at the Faculty of Islamic Economics and Business, UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan. The study employs primary data collected through a questionnaire survey administered to 80 undergraduate students from the 2021 cohort. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that Islamic financial literacy has a positive and significant effect on students’ financial behavior, suggesting that a better understanding of Islamic financial principles and practices encourages more planned and responsible financial behavior. In addition, financial self-efficacy is also found to have a positive and significant influence on financial behavior, indicating that individuals’ confidence in their ability to manage personal finances plays an important role in daily financial decision-making. These findings provide practical implications for higher education institutions to strengthen Islamic financial literacy education and enhance students’ financial self-confidence as a strategy to promote healthy and sustainable financial behavior. Future studies are recommended to expand the sample size and incorporate additional variables to obtain a more comprehensive understanding of the determinants of students’ financial behavior.